Posterior Interosseous Fascicular Constriction Within the Radial Nerve in a Diabetic Patient With Bilateral Neuralgic Amyotrophy: A Case Report - Kim, Woojun; Kang, Soo Hwan; An, Jae Young (Frontiers in Neurology, 2021)
Background: Neuralgic amyotrophy (NA) is an acute, monophasic, painful inflammatory dysimmune focal, or multifocal mononeuropathy. The lesion in NA is not always restricted to the brachial plexus but also involves individual nerves or branches. The prognosis of NA is less favorable than previously assumed, but the reasons for poor recovery remain unknown. Nerve constriction may be one of the causes of poor prognosis in NA. Case Presentation: Herein, we described a 54-year-old male with a history of type 2 diabetes in whom bilateral neuralgic amyotrophy developed with constriction of the posterior interosseous fascicle within the radial nerve. The patient experienced sudden-onset severe pain in both shoulders followed, 2 days later, by weakness in bilateral shoulders and the left forearm extensors over the subsequent month. The left forearm extensors were more severely affected than both shoulder girdle muscles. He noted a 7-kg weight loss for 1 month before pain onset. After diagnosing diabetic NA based on the clinical symptoms, imaging, and electrophysiological studies, treatment with systemic steroids improved pain and weakness in both shoulder muscles. Weakness in the left forearm extensors persisted after 1 month of steroid treatment. Follow-up ultrasound revealed constriction of the posterior interosseous fascicle within the main trunk of the left radial nerve at the elbow. Surgical exploration at 6 months after onset identified fascicle constriction, for which neurolysis was performed. Weakness in the extensors of the wrist and fingers did not improve during the 16-month follow-up. Conclusion: A single constriction of the fascicle within a peripheral nerve may often be under-recognized if NA presents with variable degrees of weakness in bilateral upper limbs. Furthermore, fascicular constriction without edema of the parent nerve may be easily missed on the initial ultrasound. A lack of early recognition of nerve constriction and delay in surgical intervention can result in unfavorable outcomes. The physician should consider the possibility of the fascicular constriction when evaluating patients suspected of brachial NA with significant weakness in the distal upper limb compared to the proximal weakness or weakness of the distal upper limb that does not improve over time.